Studi literatur: aplikasi dan potensi graphene sebagai material maju - Andrian Rian; Fatimah Arofiati Noor (Universitas Muhammadiyah Mataram, 2026)
AbstractThe development of advanced materials has led to the emergence of graphene as an innovative material with broad potential across various technological fields. This study aims to examine the characteristics, applications, advantages, and limitations of graphene through a narrative review approach. The methodology involved a literature analysis of relevant scientific publications published between 2015 and 2026, focusing on applications in electronics, energy, environmental technology, biomedicine, and construction. The review findings indicate that graphene possesses outstanding properties, including high electrical conductivity, exceptional mechanical strength, a large specific surface area, and remarkable flexibility, making it highly suitable for a wide range of modern technological applications. The discussion reveals that graphene plays a significant role in enhancing the performance of electronic devices, energy storage systems, wastewater treatment technologies, and biosensor development. However, several challenges remain, including high production costs, difficulties in large-scale synthesis, and variations in material characteristics. In conclusion, graphene demonstrates considerable potential as a next-generation material; however, further research and technological development are required to address existing challenges and facilitate its widespread industrial implementation.Keywords: graphene; applications; characteristics; nanotechnology; advanced materials.AbstrakPerkembangan material maju telah mendorong munculnya graphene sebagai salah satu material inovatif dengan potensi luas dalam berbagai bidang teknologi. Penelitian ini bertujuan untuk mengkaji karakteristik, aplikasi, serta keunggulan, dan keterbatasan graphene melalui pendekatan narrative review. Metodologi yang digunakan adalah analisis literatur dari berbagai sumber ilmiah yang relevan dalam rentang tahun 2015 hingga 2026, dengan fokus pada bidang elektronik, energi, lingkungan, biomedis, dan konstruksi. Hasil kajian menunjukkan bahwa graphene memiliki sifat unggul seperti konduktivitas listrik tinggi, kekuatan mekanik luar biasa, luas permukaan besar, serta fleksibilitas yang mendukung berbagai aplikasi teknologi modern. Dalam pembahasan ditemukan bahwa graphene berperan penting dalam meningkatkan efisiensi perangkat elektronik, penyimpanan energi, pengolahan limbah, serta pengembangan biosensor. Namun demikian, terdapat beberapa keterbatasan seperti biaya produksi tinggi, kesulitan sintesis skala besar, serta variasi karakteristik material. Kesimpulannya, graphene memiliki potensi besar sebagai material masa depan, namun memerlukan pengembangan lebih lanjut untuk mengatasi berbagai kendala yang ada serta mendukung implementasi secara luas dalam industri.Kata kunci: graphene; aplikasi; karakteristik; nanoteknologi; material maju